Rubber sealing material as well as preparation method and application thereof

By uniformly dispersing components such as N550 carbon black, silicon carbide whiskers and nano zinc oxide in ethylbutyl rubber, and using liquid phase composite technology, the problem of insufficient mechanical properties of existing sealing materials is solved, and higher hardness, tensile strength and wear resistance are achieved, meeting the long-term reliable sealing requirements of the grid equipment box for static sealing rings.

CN119842138APending Publication Date: 2025-04-18ELECTRIC POWER RES INST OF GUANGDONG POWER GRID CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510145713.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing B-butylene rubber materials used in static sealing rings of equipment boxes have shortcomings in terms of mechanical properties and are difficult to withstand complex working conditions such as assembly pressure, long-term vibration and temperature changes, resulting in poor sealing effect and service life.

Method used

A rubber sealing material is used to uniformly disperse components such as N550 carbon black, silicon carbide whiskers and nano zinc oxide in ethylbutyl rubber, and use liquid phase composite technology to ensure uniform dispersion of each component and good interface combination.

Benefits of technology

It significantly improves the hardness, tensile strength and wear resistance of the sealing material, extends the service life, and maintains a good sealing effect under humid and heat conditions, meeting the long-term reliable sealing requirements of the grid equipment box for static sealing rings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005266422200000181
    Figure BDA0005266422200000181
  • Figure BDA0005266422200000191
    Figure BDA0005266422200000191
Patent Text Reader

Abstract

The invention relates to a rubber sealing material as well as a preparation method and application thereof, and belongs to the technical field of sealing materials. The rubber sealing material disclosed by the invention is prepared from the following components in parts by weight: 100.0 parts of ethylene-butadiene rubber, 47.0 to 53.0 parts of N550 carbon black, 7.0 to 11.0 parts of silicon carbide whiskers, 6.0 to 8.0 parts of nano zinc oxide, 0.8 to 1.4 parts of stearic acid, 0.8 to 1.4 parts of an anti-aging agent MB, 0.8 to 1.4 parts of an anti-aging agent 445, 1.8 to 2.4 parts of a processing aid 935P and 1.0 to 1.2 parts of a vulcanizing agent BIBP. The rubber sealing material is prepared from the silicon carbide whiskers, the nano zinc oxide and the ethylene-butadiene rubber in a liquid-phase compounding manner, and the method can reduce the permanent deformation of the rubber sealing material due to hot and humid compression and improve the sealing performance of the sealing ring in a hot and humid environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sealing materials, and in particular to a rubber sealing material and a preparation method and application thereof. Background Art

[0002] With the continuous expansion of the scale of power grids and the continuous improvement of the requirements for power supply reliability, it is increasingly important to ensure the stable operation of electrical equipment in equipment boxes, and the sealing of equipment boxes is one of the key factors. The materials and preparation processes traditionally used for static sealing rings in equipment boxes have gradually exposed many shortcomings.

[0003] Ethylene-butadiene rubber is often used as the basic material for sealing rings because of its good weather resistance, chemical corrosion resistance, electrical insulation and certain elasticity. However, sealing rings made solely from ethylene-butadiene rubber have obvious shortcomings in mechanical properties, such as insufficient hardness and relatively low tensile strength. They are difficult to withstand the external forces caused by complex working conditions such as assembly pressure, long-term vibration and temperature changes that the equipment box faces during actual use, which in turn affects the sealing effect and service life.

[0004] At present, dry mixing is a common method for preparing composite materials containing silicon carbide whiskers, nano zinc oxide and ethylene-butadiene rubber for use in sealing rings. However, dry mixing has many defects. Due to the lack of an effective medium to promote the uniform dispersion of the components and the difficulty in ensuring good interface bonding between the components, it is easy to cause silicon carbide whiskers to agglomerate in the rubber matrix, resulting in uneven performance of the various parts of the final sealing ring, unstable physical properties, and difficulty in maintaining the sealing effect during long-term use. It cannot meet the strict requirements of the power grid equipment box for long-term reliable sealing of static sealing rings. Therefore, it is urgent to develop a new composite material preparation method and corresponding application technology that can effectively overcome the above problems. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a rubber sealing material and a preparation method and application thereof.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] In a first aspect, the present invention provides a rubber sealing material, comprising the following components in parts by weight: 100.0 parts of ethylene-butadiene rubber, 47.0-53.0 parts of N550 carbon black, 7.0-11.0 parts of silicon carbide whiskers, 6.0-8.0 parts of nano zinc oxide, 0.8-1.4 parts of stearic acid, 0.8-1.4 parts of antioxidant MB, 0.8-1.4 parts of antioxidant 445, 1.8-2.4 parts of processing aid 935P, and 1.0-1.2 parts of vulcanizing agent BIBP.

[0008] Exemplarily, the weight portion of N550 carbon black in the present invention can be any value or range value between any value in 47.0 parts, 48.0 parts, 49.0 parts, 50.0 parts, 51.0 parts, 52.0 parts, 53.0 parts. The weight portion of nano zinc oxide in the present invention can be any value or range value between any value in 6.0 parts, 7.0 parts, 8.0 parts. The weight portion of stearic acid in the present invention can be any value or range value between any value in 0.8 parts, 1.0 parts, 1.2 parts, 1.3 parts, 1.4 parts. The weight portion of antioxidant MB in the present invention can be any value or range value between any value in 0.8 parts, 1.0 parts, 1.2 parts, 1.3 parts, 1.4 parts. The weight portion of antioxidant 445 in the present invention can be any value or range value between any value in 0.8 parts, 1 parts, 1.2 parts, 1.3 parts, 1.4 parts. The weight of the processing aid 935P in the present invention can be any value among 1.8 parts, 1.9 parts, 2.0 parts, 2.1 parts, 2.2 parts, 2.3 parts, 2.4 parts, or a range between any values. The weight of the vulcanizing agent BIBP in the present invention can be any value among 1.0 parts, 1.1 parts, 1.2 parts, or a range between any values.

[0009] As a preferred embodiment of the present invention, 100 parts of ethylene-butadiene rubber, 50.0 parts of N550 carbon black, 9.0 parts of silicon carbide whiskers, 7.0 parts of nano zinc oxide, 1.1 parts of stearic acid, 1.1 parts of antioxidant MB, 1.1 parts of antioxidant 445, 2.1 parts of processing aid 935P, and 1.1 parts of vulcanizing agent BIBP.

[0010] The present invention has found that the addition amount of N550 carbon black, silicon carbide whisker and nano zinc oxide will affect the performance of the final rubber sealing material. Therefore, the present invention limits it to 47.0-53.0 parts of N550 carbon black, 7.0-11.0 parts of silicon carbide whisker, 6.0-8.0 parts of nano zinc oxide, 0.8-1.4 parts of stearic acid, 0.8-1.4 parts of antioxidant MB, 0.8-1.4 parts of antioxidant 445, 1.8-2.4 parts of processing aid 935P and 1.0-1.2 parts of vulcanizing agent BIBP, so that the rubber sealing material has good sealing effect and longer service life. The present invention selects a specific component ratio, and the obtained rubber sealing material has the advantages of good sealing effect and longer service life. In particular, when the content of ethylene-butadiene rubber is 100 parts, N550 carbon black is 50 parts, silicon carbide whisker is 9 parts, nano zinc oxide is 7 parts, stearic acid is 1.1 parts, antioxidant MB is 1.1 parts, antioxidant 445 is 1.1 parts, processing aid 935P is 2.1 parts, and vulcanizing agent BIBP is 1.1 parts, the sealing effect and durability of the rubber sealing material are the best.

[0011] As a preferred embodiment of the present invention, any of the following is satisfied:

[0012] (1) The Mooney viscosity of ethylene-butadiene rubber is ML (1+4) between 40 and 60 at 100°C, and the ethylene content is 45% to 60%;

[0013] (2) The average particle size of the N550 carbon black is 40-48 nm, and the specific surface area is 34-44 m 2 / g, oil absorption value is 114-128ml / 100g;

[0014] (3) The silicon carbide whisker has a diameter of 0.4-0.6 μm, a length of 15-20 μm, a purity of greater than or equal to 97%, and a tensile strength of greater than or equal to 2.5 GPa;

[0015] (4) The average particle size of the nano zinc oxide is 100-130nm, and the specific surface area is 50-70m 2 / g.

[0016] The present invention uses ethylene-butadiene rubber with a Mooney viscosity ML (1+4) 100°C between 40-60 and an ethylene content of 45%-60% because the Mooney viscosity range ensures that the rubber has suitable plasticity and fluidity during processing, which is convenient for subsequent mixing, molding and other operations; and the appropriate ethylene content enables it to have good elasticity while being able to better exhibit aging resistance, laying a solid foundation for the preparation of high-performance static sealing rings. Therefore, the Mooney viscosity ML (1+4) 100°C of the ethylene-butadiene rubber selected in the preferred embodiment of the present invention is 50, and the ethylene content is 50%.

[0017] The average particle size of the present invention is 40-48nm, and the specific surface area is 34-44m 2 / g, and the N550 carbon black with an oil absorption value of 114-128ml / 100g is because the carbon black in this particle size range can achieve effective physical filling in the rubber matrix, and enhance the hardness and strength of the rubber through interaction with the rubber molecular chains; the larger specific surface area helps to increase its contact area with the rubber molecules, thereby enhancing the reinforcement effect; the appropriate oil absorption value not only ensures its uniformity of dispersion during the rubber mixing process, but also has a certain regulatory effect on the processing properties of the rubber, so that the composite material has better physical properties as a whole, meets the requirements of reducing the permanent deformation of the sealing ring during use due to wet heat compression, and at the same time improves the sealing performance. Therefore, the average particle size of the N550 carbon black selected in the preferred embodiment of the present invention is 45nm, and the specific surface area is 39m 2 / g, and the oil absorption value is 121ml / 100g.

[0018] Silicon carbide whiskers play the following roles in the formulation of rubber sealing materials:

[0019] 1) Improve strength and hardness: Silicon carbide whiskers have the characteristics of high strength and high modulus. Adding them to ethylene-butadiene rubber can significantly improve the mechanical properties of rubber products such as tensile strength, tear strength and hardness, making the sealing ring less likely to deform and damage when subjected to pressure and friction, thereby better maintaining the sealing effect.

[0020] 2) Increase wear resistance: Its high hardness and high strength can effectively resist the wear of the sealing ring by external objects, reduce the amount of wear during use, and extend the service life of the sealing ring. It is especially suitable for sealing occasions that require frequent reciprocating motion or contact with rough surfaces.

[0021] 3) Improve thermal stability: Silicon carbide whiskers themselves have excellent heat resistance and can maintain good mechanical properties and chemical stability in high temperature environments. Adding them to ethylene-butadiene rubber can improve the thermal stability of the sealing ring, so that it can still maintain good elasticity and sealing performance under high temperature conditions, and is not prone to softening and deformation, thereby expanding the operating temperature range of the sealing ring.

[0022] 4) Limiting the movement of molecular chains: Silicon carbide whiskers evenly dispersed in ethylene-butadiene rubber can interact with the rubber molecular chains, limiting the thermal movement of the molecular chains, thereby reducing the dimensional changes of the rubber during temperature changes or long-term use, improving the dimensional stability of the sealing ring, and ensuring that it can fit closely with the sealing components under different working conditions to maintain a good sealing effect.

[0023] 5) High chemical stability: Silicon carbide whiskers have good chemical stability and hardly react with common chemicals such as acids, alkalis, and salts. When added to ethylene-butadiene rubber, they can improve the sealing ring's tolerance to chemical media, allowing it to maintain good performance in an environment exposed to various chemicals, and are not easily corroded or aged. They are suitable for some chemical industries and other fields that require high corrosion resistance.

[0024] 6) Improve fluidity and dispersibility: An appropriate amount of silicon carbide whiskers can improve the fluidity of ethylene-butadiene rubber and the dispersibility of fillers during the mixing process, making it easier for other compounding ingredients to be evenly distributed in the rubber matrix, thereby improving production efficiency and consistency of product quality, and is conducive to the preparation of sealing ring products with uniform performance and stable quality.

[0025] Therefore, the present invention selects silicon carbide whiskers with a diameter range of 0.4-0.6μm, a length range of 15-20μm, a purity greater than or equal to 97%, and a tensile strength greater than or equal to 2.5GPa, because the thinner diameter and appropriate length enable it to form a good reinforcement network structure in the rubber matrix. When the sealing ring is subjected to external force, the silicon carbide whiskers can effectively transfer and disperse stress, thereby improving the bearing capacity of the composite material; the high purity ensures that its own excellent performance can be fully exerted, avoiding the interference of impurities on its reinforcement effect; the strong tensile strength further strengthens its role in improving the mechanical properties of the composite material, significantly enhancing the sealing ring's ability to resist deformation when subjected to external forces such as stretching and extrusion, and ensuring the stability of the sealing effect. Therefore, the silicon carbide whiskers selected in the preferred embodiment of the present invention have a diameter range of 0.6μm, a length range of 15μm, and a tensile strength greater than or equal to 2.5GPa.

[0026] Nano zinc oxide plays the following roles in the rubber sealing material formula of the present invention:

[0027] 1) Improve vulcanization efficiency: When nano zinc oxide is mixed with stearic acid, a reaction will occur to generate zinc soap, which then forms an active complex with the accelerator. The complex can significantly improve the activity of the accelerator and accelerate the vulcanization reaction, thereby shortening the vulcanization time and improving production efficiency.

[0028] 2) Optimize the cross-linking network: It can make the rubber vulcanize to generate shorter cross-linking bonds, add new cross-linking bonds, increase the cross-linking density, make the three-dimensional network structure of rubber products more stable and complete, and thus improve the strength, hardness, elasticity and other mechanical properties of rubber products.

[0029] 3) Enhanced mechanical properties: Since nano zinc oxide has a very high specific surface area and surface activity, there is a strong interaction between it and the ethylene-butadiene rubber molecular chain. When the rubber is subjected to external forces, the nano zinc oxide particles can effectively hinder the relative sliding of the rubber molecular chain, bear and transmit stress, thereby enhancing the mechanical properties of rubber products such as tensile strength, tear resistance, and compression resistance, so that the sealing ring can better withstand various pressures and frictions during use and maintain a good sealing effect.

[0030] 4) Improve wear resistance: The addition of nano zinc oxide can improve the wear resistance of rubber, reduce the wear of the sealing ring during long-term use, extend its service life, and reduce the risk of seal failure due to wear.

[0031] 5) Improve weather resistance: Nano zinc oxide has a strong absorption and shielding effect on ultraviolet rays and infrared rays, and can effectively prevent the rubber molecular chain from being degraded and cross-linked under the influence of environmental factors such as light and heat, thereby improving the weather resistance and aging resistance of the rubber sealing ring, so that it can still maintain good physical properties and sealing performance under long-term exposure to outdoor environment or high temperature, high humidity and other harsh conditions.

[0032] 6) Stabilize the vulcanization network: During the vulcanization and use process, the hydrogen sulfide produced by the breakage of polysulfide bonds will accelerate the cracking of rubber, and nano zinc oxide will react with hydrogen sulfide to form new cross-linking bonds, stabilize the vulcanization network, and further improve the aging resistance of rubber products.

[0033] Therefore, the present invention uses an average particle size of 100-130nm and a specific surface area of ​​50-70m 2 / g of nano zinc oxide can improve its dispersibility in the material, making the nano zinc oxide more evenly dispersed in the composite material. At the same time, the nano zinc oxide in the present invention, as a vulcanization activator, can synergize with the vulcanization accelerator to effectively activate the vulcanization reaction and prompt the rubber molecules to form a tighter and more stable cross-linked network structure, thereby increasing the cross-linking density of the vulcanized rubber, optimizing the comprehensive physical properties of the composite material, and enabling the sealing ring to have sufficient strength and elastic recovery ability to cope with various deformation situations during long-term use. Therefore, the average particle size of the nano zinc oxide selected in the preferred embodiment of the present invention is 130μm, and the specific surface area is 60m 2 / g.

[0034] Stearic acid plays a vital role in the rubber processing. It can reduce the friction between rubber molecules, making the rubber easier to operate in various processing links such as mixing and vulcanization. At the same time, it helps activate the vulcanization system and promotes a more uniform and smooth vulcanization reaction, which helps to ensure the stability of the final product quality and ensure that the various performance indicators of the sealing ring meet the expected requirements.

[0035] In the present invention, antioxidant MB and antioxidant 445 are used in synergy, which can play an excellent protective role against the aging phenomenon of rubber caused by factors such as heat, oxygen, and ozone during long-term use. Antioxidant MB has a unique effect on inhibiting the catalytic aging of rubber by metal ions such as copper, while antioxidant 445 exhibits good long-term resistance to thermal oxidative aging. Through the combined effect of the two, the service life of the sealing ring can be significantly extended, so that it can still stably maintain good sealing performance in the complex environment of long-term operation of the power grid equipment box.

[0036] The addition of processing aid 935P is mainly to improve the processing performance of the rubber compound, such as processing fluidity, demoulding properties and compatibility between components. In the subsequent mixing operation of the open mill and the vulcanization molding process, good processing performance helps to ensure good product appearance quality and dimensional accuracy that meets the requirements, and can improve production efficiency and reduce production costs.

[0037] As a highly efficient vulcanizing agent, BIBP can promote cross-linking reactions between rubber molecules under specific temperature and pressure conditions to form a stable three-dimensional network structure, giving the rubber suitable mechanical properties such as hardness, elasticity, and tensile strength, ensuring that the sealing ring can effectively resist external pressure, deformation and other forces during actual use, maintain a good sealing effect, and meet the strict electrical requirements for the sealing performance of static sealing rings.

[0038] In a second aspect, the present invention provides a method for preparing a rubber sealing material, comprising the following steps:

[0039] Step 1: Add silicon carbide whiskers and nano zinc oxide to the ethylene-butadiene rubber aqueous solution in sequence, mix them evenly, and obtain a liquid phase mixed system;

[0040] Step 2: Add a flocculant to the liquid phase mixed system in an amount of 0.4% to 0.7% of the total mass of the liquid phase mixed system, and stir evenly to obtain a composite material matrix; wherein the flocculant is a polyaluminium chloride flocculant;

[0041] Step 3: drying the composite material matrix to obtain a composite material matrix in which silicon carbide whiskers and nano zinc oxide liquid phase are mixed in ethylene-butadiene rubber;

[0042] Step 4: putting the composite material matrix into an open mill and mixing for 12-20 minutes to obtain a composite material rubber;

[0043] Step 5: vulcanize the composite rubber material to obtain the rubber sealing material.

[0044] As a preferred embodiment of the present invention, the method for preparing the ethylene-butadiene rubber aqueous solution in step 1 is: putting the mixed ethylene-butadiene rubber and the coupling agent aqueous solution into a reactor for reaction to obtain the ethylene-butadiene rubber aqueous solution, wherein the coupling agent is γ-aminopropyltriethoxysilane, and the mass concentration of γ-aminopropyltriethoxysilane in the coupling agent aqueous solution is 3-5%.

[0045] As a preferred embodiment of the present invention, the input amount of ethylene-butadiene rubber is 50% of the weight of the coupling agent aqueous solution; or / and, the temperature of the reactor is 60-70°C, the stirring speed is 200-400 rpm, and the stirring time is 24h.

[0046] As a preferred embodiment of the present invention, in step 1, the stirring temperature of adding silicon carbide whiskers to the ethylene-butadiene rubber aqueous solution is 60-70°C; or / and, the stirring temperature of adding nano zinc oxide to the ethylene-butadiene rubber aqueous solution is 30-50°C.

[0047] As a preferred embodiment of the present invention, in step 3, the drying temperature is 60-70° C.; or / and the drying time is 2-4 hours.

[0048] As a preferred embodiment of the present invention, the mixing in step 4 includes the following steps:

[0049] (a) sequentially performing a wrapping operation, a thin pass operation, and a triangle wrapping operation on the composite material substrate on a roller;

[0050] (b) Stearic acid, antioxidant MB, antioxidant 445, processing aid 935P, vulcanizing agent BIBP, and N550 carbon black were added in order and mixed evenly.

[0051] As a preferred embodiment of the present invention, the sulfurization treatment in step 5 satisfies any of the following:

[0052] (a) The vulcanization temperature is 150-170°C;

[0053] (b) Vulcanization pressure is 8-12MPa,

[0054] (c) Curing time: 8-16 minutes.

[0055] In a third aspect, the present invention provides a use of the rubber sealing material as described above in a power grid equipment box.

[0056] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention manufactures a composite material by liquid-phase compounding of silicon carbide whiskers, nano-zinc oxide, and ethylene-butadiene rubber, and provides a new method for preparing a composite sealing rubber. The preparation method can evenly disperse silicon carbide whiskers and nano-zinc oxide in an ethylene-butadiene rubber matrix, thereby improving the physical properties of the sealing rubber, and increasing the hardness and tensile strength of the material, making it more suitable for use as a sealing material for power grid equipment boxes under hot and humid conditions, thereby meeting the strict requirements of power grid equipment boxes for long-term reliable sealing of static sealing rings. DETAILED DESCRIPTION

[0057] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0058] In the following examples, the information of each component is as follows:

[0059] Ethylene-butadiene rubber: Mooney viscosity ML (1+4) at 100° C. is between 40 and 60, and ethylene content is between 45% and 60%; purchased from Mitsui Chemicals, Inc., VNB-EPI.

[0060] N550 carbon black: average particle size is 40-48nm, specific surface area is 34-44m 2 / g, oil absorption value is 114-128ml / 100g; purchased from Cabot, USA, model: N550.

[0061] Silicon carbide whiskers: diameter range of 0.4-0.6 μm, length range of 15-20 μm, purity greater than or equal to 97%, tensile strength greater than or equal to 2.5 GPa; purchased from Sumitomo Chemical Co., Ltd., SiC-1.

[0062] Nano zinc oxide: average particle size is 100-130nm, specific surface area is 50-70m 2 / g; manufacturer: Shanghai Huijingya Nano New Materials Co., Ltd.; product model: HG-ZN-30.

[0063] Stearic acid: purchased from Indonesia Green Treasure, item number: 1860

[0064] γ-Aminopropyltriethoxysilane: purchased from Dow Chemical, product number: Z6020

[0065] Polyaluminium chloride flocculant: purchased from China Baowu Chemical, item number: PAC-01

[0066] Antioxidant MB: purchased from Guanghui Chemical, item number: GH-MB

[0067] Antioxidant 445: purchased from Guanghui Chemical, item number: GH-445

[0068] Processing aid 935P: purchased from Henkel, product number: Henkel 935P

[0069] Curing agent BIBP: purchased from BASF, product number: BASF BIBP

[0070] The present invention provides a rubber sealing material, comprising the following components in parts by weight: 100.0 parts of ethylene-butadiene rubber, 47.0-53.0 parts of N550 carbon black, 7.0-11.0 parts of silicon carbide whiskers, 6.0-8.0 parts of nano zinc oxide, 0.8-1.4 parts of stearic acid, 0.8-1.4 parts of antioxidant MB, 0.8-1.4 parts of antioxidant 445, 1.8-2.4 parts of processing aid 935P, and 1.0-1.2 parts of vulcanizing agent BIBP. The components of the rubber sealing material meet any of the following conditions:

[0071] (1) The Mooney viscosity of ethylene-butadiene rubber is ML (1+4) between 40 and 60 at 100°C, and the ethylene content is 45% to 60%;

[0072] (2) The average particle size of the N550 carbon black is 40-48 nm, and the specific surface area is 34-44 m 2 / g, oil absorption value is 114-128ml / 100g;

[0073] (3) The silicon carbide whisker has a diameter of 0.4-0.6 μm, a length of 15-20 μm, a purity of greater than or equal to 97%, and a tensile strength of greater than or equal to 2.5 GPa;

[0074] (4) The average particle size of the nano zinc oxide is 100-130nm, and the specific surface area is 50-70m 2 / g.

[0075] The present invention also provides a method for preparing a rubber sealing material, comprising the following steps:

[0076] Step 1: Add silicon carbide whiskers and nano zinc oxide to the ethylene-butadiene rubber aqueous solution in sequence, mix them evenly, and obtain a liquid phase mixed system; the specific steps are as follows:

[0077] 1) Preparation of coupling agent solution:

[0078] Inject pure water into the reaction kettle, control the pH value at 6-8, and the temperature at 60-70°C, then add γ-aminopropyltriethoxysilane, control its concentration at 3-5%, and stir for 1-2h to obtain a γ-aminopropyltriethoxysilane aqueous solution, i.e., a coupling agent solution.

[0079] 2) Preparation of ethylene-butadiene rubber aqueous solution:

[0080] The ethylene-butadiene rubber is mixed with an open mill, the roller distance is adjusted to 4-6 mm, the rubber is rolled, and after mixing for 10 minutes, the roller distance is adjusted to 2-3 mm for unrolling, and the sheet is left for 8 hours to obtain the ethylene-butadiene rubber film;

[0081] Use a cutter to cut the ethylene-butadiene rubber film into small pieces of 5×5 mm, and put them into the reactor of the above-mentioned γ-aminopropyltriethoxysilane aqueous solution, the amount of ethylene-butadiene rubber added is 50% of the weight of pure water; the temperature of the reactor is controlled at 60-70°C, the stirring speed is 200-400 rpm, and the stirring time is 24 hours to obtain the ethylene-butadiene rubber aqueous solution.

[0082] 3) Preparation of liquid phase mixed system:

[0083] Silicon carbide whiskers are put into an ethylene-butadiene rubber aqueous solution, the temperature of the reactor is controlled at 60-70°C, the stirring speed is 200-400 rpm, and the stirring time is 3-5h; then nano zinc oxide is added, stirring is continued, and the stirring time is controlled at 4-6h; then the temperature of the reactor is adjusted to 30-50°C, the stirring speed is increased to 400-600 rpm, and stirring is continued for 1.5-2.5 hours to obtain a liquid phase mixed system.

[0084] Step 2: Add a flocculant to the liquid phase mixed system in an amount of 0.4%-0.7% of the total mass of the liquid phase mixed system, adjust the stirring speed to 150-250 rpm, and stir for 10-20 minutes to obtain a composite material matrix; wherein the flocculant is a polyaluminium chloride flocculant;

[0085] Step 3: Dry the composite material matrix to obtain a composite material matrix in which silicon carbide whiskers and nano zinc oxide liquid are mixed in ethylene-butadiene rubber; the specific steps are as follows:

[0086] The composite material matrix is ​​transferred to the vacuum drying equipment, the drying temperature is set to 65-85°C, and the vacuum drying operation is performed according to the established vacuum drying procedure. The vacuum drying process is usually carried out in a closed drying system, and the aqueous solution is gradually removed by controlling the temperature, vacuum degree and time. The established vacuum drying procedure steps are as follows:

[0087] (a): Initial heating

[0088] Temperature setting: Heat the liquid phase mixed rubber to 65-85°C. The main purpose of this stage is to heat the rubber and aqueous solution so that the solvent can evaporate more easily.

[0089] Time control: The heating time is usually 25-35 minutes to ensure that the rubber is heated evenly as a whole, but to avoid overheating or thermal degradation of the rubber.

[0090] (b) Evaporation of aqueous solution under reduced pressure

[0091] Decompression treatment: Reduce the pressure in the drying system to 55-205 mmHg to promote the volatilization of the aqueous solution by reducing the air pressure.

[0092] Solvent evaporation: Under reduced pressure, the boiling point of the solvent will decrease and the solvent will evaporate faster. It is usually necessary to maintain the reduced pressure for 40-80 minutes.

[0093] Temperature control: Keep the temperature around 80-100℃ to ensure that the aqueous solution can evaporate without causing excessive thermal degradation of the rubber.

[0094] (c) Further drying

[0095] Further heating: After the vacuum drying is completed, the temperature is gradually increased to 105-115°C and maintained at this temperature for a period of time to further remove residual solvents and moisture to ensure that the dryness of the rubber meets the requirements.

[0096] Pressure recovery: In the final stage, the pressure can be gradually restored to normal pressure to ensure the stability of the system and prevent the rubber from getting wet.

[0097] (d) Cooling and exhaust

[0098] Cooling: After the vacuum drying, the rubber needs to be cooled at room temperature to avoid deformation of the product due to excessive temperature difference.

[0099] · Exhaust: Ensure that the steam and gas generated during the drying process are effectively discharged to avoid gas accumulation.

[0100] After standing for 24 hours, a composite material matrix of silicon carbide whiskers and nano zinc oxide liquid mixed in ethylene-butadiene rubber was obtained.

[0101] Step 4: putting the composite material matrix into an open mill and mixing for 12-20 minutes to obtain a composite material rubber; the specific steps are as follows:

[0102] (1): The roller temperature of the open mill is pre-adjusted to 50-70°C, the roller distance is set to 1.5-3.0 mm, the open mill is started, and the composite material matrix prepared as above is put into the open mill, so that the composite material matrix can be smoothly wrapped on the roller.

[0103] (2): After the roll wrapping is in good condition, various additives (stearic acid, antioxidant MB, antioxidant 445, processing aid 935P, vulcanizing agent BIBP, N550 carbon black) are added in sequence through thin-pass operation and triangle-wrapping operation to make all materials fully mixed and uniform. The total mixing time is controlled within 12-20 minutes to obtain the composite rubber material. The specific thin-pass operation and triangle-wrapping operation are: the number of thin-passes is controlled within 4-6 times, and the roller distance is adjusted to 0.8-1.5mm during each thin-pass; the number of triangle-wrapping operations is 2-4 times.

[0104] Step 5: vulcanize the composite rubber material to obtain the rubber sealing material. The specific operation is as follows: the composite rubber material is left standing for 20-24 hours, and then the rested rubber material is placed in a pre-prepared vulcanization mold, and vulcanized for 8-16 minutes at a vulcanization temperature of 150-170°C and a vulcanization pressure of 8-12MPa.

[0105] Example 1

[0106] The present embodiment provides a rubber sealing material, which includes the following components in parts by weight: 100.0 parts of ethylene-butadiene rubber, 50.0 parts of N550 carbon black, 9.0 parts of silicon carbide whiskers, 7.0 parts of nano zinc oxide, 1.1 parts of stearic acid, 1.1 parts of antioxidant MB, 1.1 parts of antioxidant 445, 2.1 parts of processing aid 935P, and 1.1 parts of vulcanizing agent BIBP.

[0107] In this embodiment, the Mooney viscosity ML (1+4) of the selected ethylene-butadiene rubber at 100° C. is 50, and the ethylene content is 50%.

[0108] In this embodiment, the average particle size of the N550 carbon black selected is 45 nm, and the specific surface area is 39 m 2 / g, and the oil absorption value is 121ml / 100g.

[0109] In this embodiment, the diameter of the selected silicon carbide whiskers is in the range of 0.5 μm, the length is in the range of 17 μm, the purity is greater than or equal to 97%, and the tensile strength is greater than or equal to 2.5 GPa.

[0110] In this embodiment, the average particle size of the nano zinc oxide selected is 120nm and the specific surface area is 60m 2 / g.

[0111] The preparation method of the rubber sealing material of embodiment 1 is as follows:

[0112] 1. Preparation of liquid phase mixing system:

[0113] 1) Preparation of coupling agent solution:

[0114] Pure water was injected into the reaction kettle, the pH value was controlled at 6, the temperature was controlled at 60°C, and then γ-aminopropyltriethoxysilane was added, the concentration was controlled at 4%, and the stirring time was controlled at 1h to obtain a γ-aminopropyltriethoxysilane aqueous solution, i.e., a coupling agent solution.

[0115] 2) Preparation of ethylene-butadiene rubber aqueous solution:

[0116] The ethylene-butadiene rubber is mixed on an open mill, the roller distance is adjusted to 4 mm, the rubber is rolled, and after mixing for 10 minutes, the roller distance is adjusted to 2 mm for unrolling, and the sheet is left for 8 hours to obtain the ethylene-butadiene rubber film;

[0117] Use a cutter to cut the ethylene-butadiene rubber film into small pieces of 5×5 mm and put them into the reactor of the above-mentioned γ-aminopropyltriethoxysilane aqueous solution. The amount of ethylene-butadiene rubber added is 50% of the weight of pure water. The temperature of the reactor is controlled at 60°C, the stirring speed is 200 rpm, and the stirring time is 24 hours to obtain the ethylene-butadiene rubber aqueous solution.

[0118] 3) Preparation of liquid phase mixed system:

[0119] Silicon carbide whiskers were put into an ethylene-butadiene rubber aqueous solution, the temperature of the reactor was controlled at 60°C, the stirring speed was 200 rpm, and the stirring time was 3 hours; then nano zinc oxide was added, stirring was continued, and the stirring time was controlled at 6 hours; then the temperature of the reactor was adjusted to 50°C, the stirring speed was increased to 400 rpm, and stirring was continued for 1.5 hours to obtain a liquid phase mixed system.

[0120] 2. Preparation of composite material matrix:

[0121] Add polyaluminium chloride flocculant to the liquid phase mixed system in an amount controlled at 0.4% of the total mass of the mixed system, adjust the stirring speed to 150 rpm, and stir for 10 minutes.

[0122] 3. Drying treatment of composite material matrix:

[0123] The above-mentioned rubber material is transferred to the reduced pressure drying equipment, the drying temperature is set to 85°C, and the drying operation is performed according to the established reduced pressure drying program. The reduced pressure drying process is usually carried out in a closed drying system, and the aqueous solution is gradually removed by controlling the temperature, reduced pressure degree and time.

[0124] Step 1: Initial heating

[0125] Temperature setting: Heat the liquid phase mixed rubber to 85°C. The main purpose of this stage is to heat the rubber and aqueous solution so that the solvent can evaporate more easily.

[0126] Time control: The heating time is usually 25 minutes to ensure that the rubber is heated evenly, but to avoid overheating or thermal degradation of the rubber.

[0127] Step 2: Evaporation of aqueous solution under reduced pressure

[0128] Decompression treatment: Reduce the pressure in the drying system to 55 mmHg to promote the volatilization of the aqueous solution by reducing the air pressure.

[0129] Solvent evaporation: Under reduced pressure, the boiling point of the solvent will decrease and the solvent will evaporate faster. It is usually necessary to maintain the reduced pressure for 40 minutes.

[0130] Temperature control: Keep the temperature at around 80°C to ensure that the aqueous solution can evaporate without causing excessive thermal degradation of the rubber.

[0131] Step 3: Further drying

[0132] Further heating: After the vacuum drying is completed, the temperature is gradually increased to 105°C and maintained for a period of time to further remove residual solvents and moisture to ensure that the dryness of the rubber meets the requirements.

[0133] Pressure recovery: In the final stage, the pressure can be gradually restored to normal pressure to ensure the stability of the system and prevent the rubber from getting wet.

[0134] Step 4: Cooling and exhaust

[0135] Cooling: After the vacuum drying, the rubber needs to be cooled at room temperature to avoid deformation of the product due to excessive temperature difference.

[0136] · Exhaust: Ensure that the steam and gas generated during the drying process are effectively discharged to avoid gas accumulation.

[0137] After standing for 24 hours, a composite material matrix of silicon carbide whiskers and nano zinc oxide liquid mixed in ethylene-butadiene rubber was obtained.

[0138] 4. Preparation of composite rubber:

[0139] The roller temperature of the open mill was pre-adjusted to 50° C., the roller distance was set to 1.5 mm, the open mill was started, and the composite material matrix prepared as above was put into the open mill so that the composite material matrix could be smoothly wrapped on the roller.

[0140] After the roller is in good condition, various additives (stearic acid, antioxidant MB, antioxidant 445, processing aid 935P, vulcanizing agent BIBP, N550 carbon black) are added in sequence through thin-pass operation and triangle-packing operation to make all materials fully mixed and uniform. The total mixing time is controlled within 12 minutes to obtain the composite rubber compound.

[0141] The specific thin-pass operation and triangle-packing operation are as follows: the number of thin-pass operations is controlled at 6 times, and the roller distance is adjusted to 0.8mm for each thin-pass operation; the number of triangle-packing operations is 2 times.

[0142] 5. Vulcanization treatment:

[0143] The composite rubber material was left to stand for 20 hours, and then the rested rubber material was placed in a pre-prepared vulcanization mold, and vulcanized for 8 minutes at a vulcanization temperature of 150°C and a vulcanization pressure of 8MPa.

[0144] Example 2

[0145] The present embodiment provides a rubber sealing material, which includes the following components in parts by weight: 100.0 parts of ethylene-butadiene rubber, 47.0 parts of N550 carbon black, 7.0 parts of silicon carbide whiskers, 6.0 parts of nano zinc oxide, 0.8 parts of stearic acid, 0.8 parts of antioxidant MB, 0.8 parts of antioxidant 445, 1.8 parts of processing aid 935P, and 1.0 parts of vulcanizing agent BIBP.

[0146] In this embodiment, the Mooney viscosity ML (1+4) of the selected ethylene-butadiene rubber at 100° C. is 40, and the ethylene content is 45%.

[0147] In this embodiment, the average particle size of the N550 carbon black selected is 40 nm and the specific surface area is 34 m 2 / g, and the oil absorption value is 114ml / 100g.

[0148] In this embodiment, the diameter of the selected silicon carbide whiskers is in the range of 0.4 μm, the length is in the range of 15 μm, the purity is greater than or equal to 97%, and the tensile strength is greater than or equal to 2.5 GPa.

[0149] In this embodiment, the average particle size of the selected nano zinc oxide is 100nm and the specific surface area is 50m 2 / g.

[0150] The preparation method of the rubber sealing material of Example 2 is as follows:

[0151] 1. Preparation of liquid phase mixing system:

[0152] 1) Preparation of coupling agent solution:

[0153] Pure water was injected into the reaction kettle, the pH value was controlled at 8, the temperature was controlled at 70°C, and then γ-aminopropyltriethoxysilane was added, the concentration was controlled at 3%, and the stirring time was controlled at 2h to obtain a γ-aminopropyltriethoxysilane aqueous solution, i.e., a coupling agent solution.

[0154] 2) Preparation of ethylene-butadiene rubber aqueous solution:

[0155] The ethylene-butadiene rubber is mixed on an open mill, the roller distance is adjusted to 6 mm, the rubber is rolled, and after mixing for 10 minutes, the roller distance is adjusted to 3 mm for unrolling, and the ethylene-butadiene rubber film is obtained after being left for 8 hours;

[0156] Use a cutter to cut the ethylene-butadiene rubber film into small pieces of 5×5 mm and put them into the reactor of the above-mentioned γ-aminopropyltriethoxysilane aqueous solution. The amount of ethylene-butadiene rubber added is 50% of the weight of pure water. The temperature of the reactor is controlled at 70°C, the stirring speed is 200 rpm, and the stirring time is 24 hours to obtain the ethylene-butadiene rubber aqueous solution.

[0157] 3) Preparation of liquid phase mixed system:

[0158] Silicon carbide whiskers were put into an ethylene-butadiene rubber aqueous solution, the temperature of the reactor was controlled at 70°C, the stirring speed was 400 rpm, and the stirring time was 5 hours; then nano zinc oxide was added, stirring was continued, and the stirring time was controlled at 4 hours; then the temperature of the reactor was adjusted to 30°C, the stirring speed was increased to 600 rpm, and stirring was continued for 1.5 hours to obtain a liquid phase mixed system.

[0159] 2. Preparation of composite material matrix:

[0160] Add polyaluminium chloride flocculant to the liquid phase mixed system in an amount controlled to 0.7% of the total mass of the mixed system, adjust the stirring speed to 250 rpm, and stir for 10 minutes.

[0161] 3. Drying treatment of composite material matrix:

[0162] The above-mentioned rubber material is transferred to the reduced pressure drying equipment, the drying temperature is set to 85°C, and the drying operation is performed according to the established reduced pressure drying program. The reduced pressure drying process is usually carried out in a closed drying system, and the aqueous solution is gradually removed by controlling the temperature, reduced pressure degree and time.

[0163] Step 1: Initial heating

[0164] Temperature setting: Heat the liquid phase mixed rubber to 65°C. The main purpose of this stage is to heat the rubber and aqueous solution so that the solvent can evaporate more easily.

[0165] Time control: The heating time is usually 35 minutes to ensure that the rubber is heated evenly, but to avoid overheating or thermal degradation of the rubber.

[0166] Step 2: Evaporation of aqueous solution under reduced pressure

[0167] Decompression treatment: Reduce the pressure in the drying system to 205 mmHg to promote the volatilization of the aqueous solution by reducing the air pressure.

[0168] Solvent evaporation: Under reduced pressure, the boiling point of the solvent will decrease and the solvent will evaporate faster. It is usually necessary to maintain the reduced pressure for 40 minutes.

[0169] ●Temperature control: Keep the temperature at around 80°C to ensure that the aqueous solution can evaporate without causing excessive thermal degradation of the rubber.

[0170] Step 3: Further drying

[0171] Further heating: After the vacuum drying is completed, the temperature is gradually increased to 115°C and maintained at this temperature for a period of time to further remove residual solvents and moisture to ensure that the dryness of the rubber meets the requirements.

[0172] Pressure recovery: In the final stage, the pressure can be gradually restored to normal pressure to ensure the stability of the system and prevent the rubber from getting wet.

[0173] Step 4: Cooling and exhaust

[0174] Cooling: After the vacuum drying, the rubber needs to be cooled at room temperature to avoid deformation of the product due to excessive temperature difference.

[0175] ● Exhaust: Ensure that the steam and gas generated during the drying process are effectively discharged to avoid gas accumulation.

[0176] After standing for 24 hours, a composite material matrix of silicon carbide whiskers and nano zinc oxide liquid mixed in ethylene-butadiene rubber was obtained.

[0177] 4. Preparation of composite rubber:

[0178] The roller temperature of the open mill was pre-adjusted to 50° C., the roller distance was set to 1.5 mm, the open mill was started, and the composite material matrix prepared as above was put into the open mill so that the composite material matrix could be smoothly wrapped on the roller.

[0179] After the roller is in good condition, various additives (stearic acid, antioxidant MB, antioxidant 445, processing aid 935P, vulcanizing agent BIBP, N550 carbon black) are added in sequence through thin-pass operation and triangle-packing operation to make all materials fully mixed and uniform. The total mixing time is controlled at 12-20 minutes to obtain the composite rubber material.

[0180] The specific thin-pass operation and triangle-packing operation are as follows: the number of thin-pass operations is controlled at 4 times, and the roller distance is adjusted to 0.8-1.5mm for each thin-pass operation; the number of triangle-packing operations is 4 times.

[0181] 5. Vulcanization treatment:

[0182] The composite rubber material was left to stand for 20 hours, and then the rested rubber material was placed in a pre-prepared vulcanization mold, and vulcanized for 16 minutes at a vulcanization temperature of 150° C. and a vulcanization pressure of 12 MPa.

[0183] Example 3

[0184] The difference between Example 3 and Example 1 is that the weight percentage of each component is different and the parameters of some components are different, specifically: 100.0 parts of ethylene-butadiene rubber, 53.0 parts of N550 carbon black, 11.0 parts of silicon carbide whiskers, 8.0 parts of nano zinc oxide, 1.4 parts of stearic acid, 1.4 parts of antioxidant MB, 1.4 parts of antioxidant 445, 2.4 parts of processing aid 935P, and 1.2 parts of vulcanizing agent BIBP.

[0185] In this embodiment, the Mooney viscosity ML (1+4) of the selected ethylene-butadiene rubber at 100° C. is 60, and the ethylene content is 60%.

[0186] In this embodiment, the average particle size of the N550 carbon black selected is 48 nm and the specific surface area is 44 m 2 / g, and the oil absorption value is 128ml / 100g.

[0187] In this embodiment, the diameter of the selected silicon carbide whiskers is in the range of 0.6 μm, the length is in the range of 20 μm, the purity is greater than or equal to 97%, and the tensile strength is greater than or equal to 2.5 GPa.

[0188] In this embodiment, the average particle size of the nano zinc oxide selected is 130nm and the specific surface area is 70m 2 / g.

[0189] The difference between the preparation method of this embodiment and that of embodiment 1 is that the concentration of the γ-aminopropyltriethoxysilane added is controlled at 5%; and the amount of the polyaluminium chloride flocculant added is controlled at 0.8% of the total mass of the mixed system.

[0190] Comparative Example 1

[0191] The difference between Comparative Example 1 and Example 1 is that ethylene-butadiene rubber, nano zinc oxide and silicon carbide whiskers are mixed by dry method, wherein the addition amount of the components is the same as that of Example 1; the specific preparation method is as follows:

[0192] Pre-adjust the roller temperature of the open mill to 50°C, set the roller distance to 1.5mm, start the open mill, put the ethylene-butadiene rubber into the open mill, and make the ethylene-butadiene rubber roll-wrapped. After the roll-wrapping is in good condition, first add N550 carbon black and processing aid 935P. After the powder is completely absorbed, add silicon carbide whiskers, nano zinc oxide, stearic acid, antioxidant MB, antioxidant 445, and vulcanizer BIBP in order. After the powder is completely absorbed, mix all kinds of materials evenly, and the total mixing time is controlled within 15 minutes. Put the rubber material down and adjust the roller distance to 0.8mm. Put the rubber material in and continue mixing. The number of thin-pass rolling is controlled to 6 times, and the number of triangle bagging operations is 2 times. Adjust the roller distance to 4.0mm, and the rubber material is parked for 24 hours before the detection procedure.

[0193] Comparative Example 2

[0194] The difference between Comparative Example 2 and Example 1 is that ethylene-butadiene rubber and silicon carbide whiskers are mixed by liquid phase, and nano zinc oxide is mixed by dry method, wherein the addition amount of the components is the same as that of Example 1; the specific preparation method is as follows:

[0195] Pre-adjust the roller temperature of the open mill to 50°C, set the roller distance to 1.5mm, start the open mill, put the liquid phase mixed rubber of ethylene-butadiene rubber and silicon carbide whiskers into the open mill, and make the ethylene-butadiene rubber roll-wrapped. After the roll-wrapping is in good condition, first add N550 carbon black and processing aid 935P. After the powder is completely absorbed, add nano zinc oxide, stearic acid, antioxidant MB, antioxidant 445, and vulcanizer BIBP in order. After the powder is completely absorbed, mix all kinds of materials evenly, and the total mixing time is controlled within 15 minutes. Put the rubber material down and adjust the roller distance to 0.8mm. Put the rubber material in and continue mixing. The number of thin-pass rolling is controlled to 6 times, and the number of triangle bagging operations is 2 times. Adjust the roller distance to 4.0mm, and the rubber material is parked for 24 hours before the detection procedure.

[0196] Comparative Example 3

[0197] The difference between Comparative Example 3 and Example 1 is that ethylene-butadiene rubber and nano zinc oxide are mixed by liquid phase, and silicon carbide whiskers are mixed by dry method, wherein the addition amount of the components is the same as that of Example 1; the specific preparation method is as follows: 、

[0198] Pre-adjust the roller temperature of the open mill to 50℃, set the roller distance to 1.5mm, start the open mill, put the liquid phase mixed rubber of ethylene-butadiene rubber and nano zinc oxide into the open mill, and make the ethylene-butadiene rubber roll-wrapping operation. After the roll-wrapping is in good condition, first add N550 carbon black and processing aid 935P. After the powder is completely absorbed, add silicon carbide whiskers, stearic acid, antioxidant MB, antioxidant 445, and vulcanizer BIBP in order. After the powder is completely absorbed, mix all kinds of materials evenly, and the total mixing time is controlled within 15 minutes. Put the rubber sheet down and adjust the roller distance to 0.8mm. Put the rubber material in and continue mixing. The number of thin-pass rolling is controlled to 6 times, and the number of triangle bagging operations is 2 times. Adjust the roller distance to 4.0mm, and the rubber sheet is parked for 24 hours before the detection procedure.

[0199] Comparative Example 4

[0200] The difference between Comparative Example 4 and Example 1 is that the antioxidant 445 is not added, and the weight of the antioxidant MB is equal to the total amount of the two antioxidants in Example 2.

[0201] Comparative Example 5

[0202] The difference between Comparative Example 5 and Example 1 is that antioxidant MB is not added, and the weight of antioxidant 445 is equal to the total amount of the two antioxidants in Example 2.

[0203] Comparative Example 6

[0204] The difference between Comparative Example 6 and Example 1 is that the addition amount of each component is different, as follows:

[0205] 100 parts of ethylene-butadiene rubber, 45.0 parts of N550 carbon black, 5.0 parts of silicon carbide whiskers, 4.0 parts of nano zinc oxide, 0.6 parts of stearic acid, 0.6 parts of antioxidant MB, 0.6 parts of antioxidant 445, 1.6 parts of processing aid 935P, and 0.6 parts of vulcanizing agent BIBP.

[0206] Comparative Example 7

[0207] The difference between Comparative Example 7 and Example 1 is that the addition amount of each component is different, as follows:

[0208] 100.0 parts of ethylene-butadiene rubber, 55.0 parts of N550 carbon black, 13.0 parts of silicon carbide whiskers, 9.0 parts of nano zinc oxide, 1.6 parts of stearic acid, 1.6 parts of antioxidant MB, 1.6 parts of antioxidant 445, 2.6 parts of processing aid 935P, and 1.4 parts of vulcanizing agent BIBP.

[0209] Comparative Example 8

[0210] The difference between Comparative Example 8 and Example 1 is that the average particle size of N550 carbon black is 35 nm.

[0211] Comparative Example 9

[0212] The difference between Comparative Example 9 and Example 1 is that the average particle size of N550 carbon black is 53 nm.

[0213] Comparative Example 10

[0214] The difference between Comparative Example 10 and Example 1 is that the diameter of the silicon carbide whisker is 0.2 μm.

[0215] Comparative Example 11

[0216] The difference between Comparative Example 11 and Example 1 is that the diameter of the silicon carbide whisker is 0.8 μm.

[0217] Comparative Example 12

[0218] The difference between Comparative Example 12 and Example 1 is that the length of the silicon carbide whisker is 12 μm.

[0219] Comparative Example 13

[0220] The difference between Comparative Example 13 and Example 1 is that the length of the silicon carbide whisker is 25 μm.

[0221] Comparative Example 14

[0222] The difference between Comparative Example 14 and Example 1 is that the specific surface area of ​​nano zinc oxide is 45m 2 / g.

[0223] Comparative Example 15

[0224] The difference between Comparative Example 15 and Example 1 is that the specific surface area of ​​nano zinc oxide is 75m 2 / g.

[0225] Comparative Example 16

[0226] The difference between Comparative Example 16 and Example 1 is that the coupling agent is γ-(2,3-epoxypropoxy)propyltrimethoxysilane.

[0227] Comparative Example 17

[0228] The difference between Comparative Example 17 and Example 1 is that the coupling agent is γ-methacryloxypropyltrimethoxysilane.

[0229] Comparative Example 18

[0230] The difference between Comparative Example 18 and Example 1 is that the flocculant is aluminum sulfate.

[0231] Comparative Example 19

[0232] The difference between Comparative Example 19 and Example 1 is that the flocculant is ferric chloride.

[0233] The preparation method of the rubber sealing material of the above-mentioned comparative examples 4-19 is the same as that of Example 1.

[0234] Test Case

[0235] The rubber sealing materials prepared in the examples and comparative examples were tested for physical properties, and the test method was as follows:

[0236] 1. Shore hardness test method: GB / T 531.1-2008 method;

[0237] 2. Tensile strength test method: GB / T 528-2021 method;

[0238] 3. Elongation at break test method: GB / T 528-2021 method is adopted;

[0239] 4. 100% elongation stress test method: GB / T 528-2021 method is adopted;

[0240] 5. Wet heat compression permanent deformation test method: GB / T 7759-2020 method is adopted.

[0241] The results are shown in Table 1 below:

[0242] Table 1: Physical property test results of rubber sealing materials of examples and comparative examples

[0243]

[0244]

[0245] As can be seen from the above table, in Examples 1-3, silicon carbide whiskers, nano-zinc oxide, and ethylene-butadiene rubber are used to manufacture composite materials by liquid phase compounding. This preparation method can evenly disperse silicon carbide whiskers and nano-zinc oxide in the ethylene-butadiene rubber matrix, thereby improving the Shore hardness, tensile strength, elongation at break, and tensile stress of the sealing rubber, and reducing the permanent deformation rate of wet heat compression, thereby improving the physical properties of the material.

[0246] It can be seen from Comparative Examples 1-3 that due to the dry mixing adopted in Comparative Examples 1-3, the overall performance of the rubber sealing material obtained is inferior to that of the embodiment. It can be seen that the wet method for preparing rubber of the present invention can improve the hardness and tensile strength of the rubber, thereby improving the physical properties of the sealing rubber.

[0247] It can be seen from Comparison 4-19 that the performance of the rubber materials of Comparative Examples 4-19 is inferior to that of the embodiment. It can be seen that the amount of raw materials used in the sealing rubber and the specifications of the raw materials are also particularly important to the performance of the sealing rubber. The present invention has found that when the amount of each raw material is within the amount range of the present invention and the specifications of each raw material are within the selection range of the present invention, the hardness and tensile strength of the rubber can be improved, thereby improving the physical properties of the sealing rubber.

[0248] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A rubber sealing material, characterized in that: The invention comprises the following components in parts by weight: 100.0 parts of ethylene-butadiene rubber, 47.0-53.0 parts of N550 carbon black, 7.0-11.0 parts of silicon carbide whisker, 6.0-8.0 parts of nano zinc oxide, 0.8-1.4 parts of stearic acid, 0.8-1.4 parts of antioxidant MB, 0.8-1.4 parts of antioxidant 445, 1.8-2.4 parts of processing aid 935P and 1.0-1.2 parts of vulcanizing agent BIBP.

2. The rubber sealing material according to claim 1, characterized in that: Meet any of the following: (1) The Mooney viscosity of ethylene-butadiene rubber is ML (1+4) between 40 and 60 at 100°C, and the ethylene content is 45% to 60%; (2) The average particle size of the N550 carbon black is 40-48 nm, and the specific surface area is 34-44 m 2 / g, oil absorption value is 114-128ml / 100g; (3) The silicon carbide whisker has a diameter of 0.4-0.6 μm, a length of 15-20 μm, a purity of greater than or equal to 97%, and a tensile strength of greater than or equal to 2.5 GPa; (4) The average particle size of the nano zinc oxide is 100-130nm, and the specific surface area is 50-70m 2 / g.

3. A method for preparing a rubber sealing material as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Add silicon carbide whiskers and nano zinc oxide to the ethylene-butadiene rubber aqueous solution in sequence, mix them evenly, and obtain a liquid phase mixed system; Step 2: Add a flocculant to the liquid phase mixed system in an amount of 0.4% to 0.7% of the total mass of the liquid phase mixed system, and stir evenly to obtain a composite material matrix; wherein the flocculant is a polyaluminium chloride flocculant; Step 3: drying the composite material matrix to obtain a composite material matrix in which silicon carbide whiskers and nano zinc oxide liquid phase are mixed in ethylene-butadiene rubber; Step 4: putting the composite material matrix into an open mill for mixing to obtain a composite material rubber; Step 5: vulcanize the composite rubber material to obtain the rubber sealing material.

4. The preparation method according to claim 3, characterized in that: The preparation method of the ethylene-butadiene rubber aqueous solution in step 1 is: putting the mixed ethylene-butadiene rubber and coupling agent aqueous solution into a reactor for reaction to obtain the ethylene-butadiene rubber aqueous solution, wherein the coupling agent is γ-aminopropyltriethoxysilane, and the mass concentration of γ-aminopropyltriethoxysilane in the coupling agent aqueous solution is 3-5%.

5. The preparation method according to claim 4, characterized in that: The input amount of ethylene-butadiene rubber is 50% of the weight of the coupling agent aqueous solution; or / and, the temperature of the reaction kettle is 60-70° C., the stirring speed is 200-400 rpm, and the stirring time is 24 hours.

6. The preparation method according to claim 3, characterized in that: In the step 1, the silicon carbide whisker is added to the ethylene-butadiene rubber aqueous solution and the stirring temperature is 60-70° C.; or / and, the nano zinc oxide is added to the ethylene-butadiene rubber aqueous solution and the stirring temperature is 30-50° C.

7. The preparation method according to claim 3, characterized in that: In step 3, the drying temperature is 60-70° C.; or / and the drying time is 2-4 hours.

8. The preparation method according to claim 3, characterized in that: The mixing in step 4 comprises the following steps: (a) sequentially performing a wrapping operation, a thin pass operation, and a triangle wrapping operation on the composite material substrate on a roller; (b) Stearic acid, antioxidant MB, antioxidant 445, processing aid 935P, vulcanizing agent BIBP, and N550 carbon black were added in order and mixed evenly.

9. The preparation method according to claim 3, characterized in that: The sulfurization treatment in step 5 satisfies any of the following: (a) The vulcanization temperature is 150-170°C; (b) Vulcanization pressure is 8-12MPa, (c) Curing time: 8-16 minutes.

10. Use of the rubber sealing material according to claim 1 in a power grid equipment box.

Citation Information

Cited By

  • Perfluoroether rubber material easy to process, high in toughness and low in thermal expansion coefficient as well as preparation method and application of perfluoroether rubber material

    CN122404944A